Disability Studies in the Belly of the Beast - Block, Pamela (Disability Studies Quarterly, 2004)
This article contains information on how to develop DS activities on the university level with particular attention to teaching DS in the health sciences. The author discusses: (1) creating an on-campus DS community through interdisciplinary discussion groups for faculty and staff; (2) navigating the course approval process; (3) building course content; (4) teaching and grading strategies, and; (5) developing an undergraduate DS concentration as part of a bachelor's degree in health science.